Injektabel Komposit Hydroksiapatit-Gelatin sebagai Sistem Penghantaran Alendronat - Aniek Setiya Budiatin; Junaidi Khotib; Didik Hasmono; Samirah Samirah (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2016)
Background: Bisphosphonates, such as alendronate (ALE), have been known to be effective in the treatment of bone cancer and osteoporosis. However, it has been reported that the systemic administration of ALE causes a considerable side effect. Thus, the formulation injectable bone substitute (IBS) for local administration of ALE, which functions as drug delivery system (DDS) as well as filling agent in osteoporosis-induced bone fracture, is needed. Objective: To establish the biodegradable and biocompatible formulation for ALE in injectable form which supports the drug delivery system and acts as filling agent in bone fracture. Methods: Hydroxyapatite (HA) was added to the mixture of gelatin and hydroxypropyl methyl cellulose (GEL-HPMC). ALE was added to the mixture and semisolid form was prepared for granulation. The dried granule, as injectable matrix, was grinded and mixed with appropriate amount of Na2HPO4. Results: Porosity of injectable form was higher than those of granule form. Injectable semisolid form was produced by adding 0.8 mL Na2HPO4 on each gram of granule with 10-12 min setting time. MTT assay showed that matrix was biocompatible showed by more than 100% viability. In vitro dissolution study showed that ALE was slowly released in more than 20 days. Conclusions: The formula of IBS using HA-GEL-HPMC may act as an effective drug delivery system for local administration of ALE in bone fracture.